Two new species and new record of Amphinemura (Plecoptera: Nemouridae) from northern China - Li, Weihai; Teslenko, Valentina A.; Yang, Ding (Zootaxa, 2020)
Amphinemura changbaishana sp. nov. and Amphinemura qiliana sp. nov. (Plecoptera: Nemouridae) are described and illustrated as two new stonefly species from northern China. Affinities of the new taxa with similar regional species of Amphinemura are discussed. Amphinemura verrucosa Zwick, 1973 is reported from China for the first time.